Limits of Object Persistence: Young Infants Perceive Continuity of Vertical and Horizontal Trajectories, But Not 45‐Degree Oblique Trajectories. (27th October 2016) - Bremner, J. Gavin; Slater, Alan M.; Mason, Uschi C.; Spring, Jo; Johnson, Scott P.
Abstract : Previous research indicated that 4‐month‐old infants perceive continuity of objects moving on horizontal trajectories but appear to have difficulty processing occlusion events involving oblique trajectories. However, because perception of continuity of vertical trajectories has not been tested, it is uncertain whether this indicates a specific deficit for oblique trajectories or a specific advantage for horizontal trajectories. We evaluated the contribution of trajectory orientation and the form of occlusion in three experiments with one hundred and forty‐four 4‐month‐olds. Infants perceived continuity of horizontal and vertical trajectories under all conditions presented. However, they did not perceive continuity of an oblique (45°) trajectory under any condition. Thus, 4‐month‐olds appear unable to process continuity of a 45° trajectory. In a fourth experiment with forty‐eight 6‐ and 8‐month‐old infants, we demonstrated that by 6 months, infants' difficulty with oblique trajectories is overcome. We suggest that young infants' difficulty with markedly oblique trajectories likely relates to immature eye movement control.